2018
DOI: 10.1186/s12985-018-1037-0
|View full text |Cite
|
Sign up to set email alerts
|

Human adenovirus load in respiratory tract secretions are predictors for disease severity in children with human adenovirus pneumonia

Abstract: BackgroundPneumonia is a serious public health issue and is concerned around the world. This study is to investigate the association between viral load in children with human adenovirus (HAdV) pneumonia and disease severity.MethodsA total of 1313 cases of children hospitalized in Hunan Provincial People’s Hospital due to community acquired pneumonia (CAP) from April 2011 to May 2014 were enrolled in this study. Samples of nasopharyngeal aspirate were collected for the cohort. WHO criteria for CAP grading was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 30 publications
3
55
1
4
Order By: Relevance
“…This results indicate the importance of the use of a nucleic acid-based test for routine diagnosis of adenovirus infection. Adenovirus is an important respiratory pathogen, and the positive rate (78.13%) in our study was significantly higher than that (13.3%) in Hunan [18], which may be related to the number of specimens and selected patients in our study. Furthermore, culture and mNGS were equally sensitive, as only one case of H. influenzae was missed by mNGS.…”
Section: Discussioncontrasting
confidence: 66%
“…This results indicate the importance of the use of a nucleic acid-based test for routine diagnosis of adenovirus infection. Adenovirus is an important respiratory pathogen, and the positive rate (78.13%) in our study was significantly higher than that (13.3%) in Hunan [18], which may be related to the number of specimens and selected patients in our study. Furthermore, culture and mNGS were equally sensitive, as only one case of H. influenzae was missed by mNGS.…”
Section: Discussioncontrasting
confidence: 66%
“…Most adenovirus infections are self-limited, while pneumonia is the most serious disease caused by HAdV infection in children ( Shi et al, 2020 ). The severity of HAdV infection is significantly correlated with serotype ( Xie et al, 2018b ). Compared with infected HAdV-3, children infected with HAdV-7 had a higher incidence of severe pneumonia, higher requirement for oxygen, and a longer length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Because the severity of adenovirus pneumonia in children varies, we explored tools that could be used to predict the severity of this disease and guide management decisions. A previous study of immunocompetent children showed that adenovirus load in respiratory tract secretions was a predictor of the severity of adenovirus pneumonia [ 8 ]. Other previous studies in immunocompromised children have demonstrated an association between adenovirus viremia and disease severity [ 3 5 ].…”
Section: Discussionmentioning
confidence: 99%